When Culture Meets Text: Examining the Relationship between Students’ Reading Comprehension and Cultural Competence - Franciel S. Mado; Leah A. H-Noor; Prences Mae M. Langga; Jake B. Doloricon; Ella L. Sala; Sittie Aina T. Pandapatan (Journal of English Language Teaching and Applied Linguistics, 2025)
The reading comprehension of students in the Philippines nowadays is poor, which comes with various reasons and factors, specifically their reading comprehension when exposed to an unfamiliar culture. Hence, this study investigated the relationship between reading comprehension and cultural competence among Grade 10 students from Bataraza National High School in Bataraza, Palawan, during the academic year 2024-2025. It evaluated the respondents’ reading comprehension skills across three cultural contexts: indigenous, local, and foreign culture-related texts. Also, it examined how respondents’ familiarity and understanding of these cultural contexts influenced their reading comprehension abilities. Moreover, pedagogical implications were drawn from the data, which focus on enhancing students’ comprehension abilities through culturally responsive teaching methods and on promoting inclusivity in the classroom. This study used a multiple-choice questionnaire as instrument. Findings show that respondents performed better on texts that are related to indigenous culture, followed by local and foreign cultures. Further, the study revealed no statistically significant difference in reading comprehension scores between respondents reading indigenous culture-related texts and those reading local culture-related texts. However, an important difference was observed in reading comprehension scores when comparing local culture-related texts to foreign culture-related texts. A significant difference was found between reading comprehension scores for indigenous and foreign culture-related texts. This suggests that cultural familiarity plays a vital role in reading comprehension.